Illness behaviour of some white south africans - Merryl Hammond (AOSIS, 1981)
THE author's interest was recently aroused by coming into contact with some of the literature dealing with "illness behaviour".1121 The study of illness behaviour basically involves an attempt to understand: what makes different people decide that they are ill; what action they take; how long they delay; what influences their decisions; and so on. In other words, there is a basic assumption that people perceive illness differently and that they react to it differently. The author believes it is essential for all health workers to be aware of the complexities of illness behaviour and therefore presents some of the data gathered recently in a study of illness behaviour among White adults in Durban.